JAMBAN SEHAT DAN PENYAKIT BERBASIS LINGKUNGAN DI MUARA KUMPE - Armaidi Darmawan; Ima Maria; Wahyu Indah Dewi Aurora; Erny Kusdiyah; Nuriyah Nuriyah (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2023)
Introduction: An unhealthy environment can cause various diseases. Environmental-based diseases are a concern because they are among the 10 most common diseases in public health centers throughout Indonesia. The use of healthy latrines is one of the indicators contained in the achievement of Community-Based Total Sanitation, Clean and Healthy Living Behavior (PHBS) indicators, and Healthy Indonesia Program Process with Family Approach (PIS-PK) indicators. Objective: This study aims to describe the application of healthy latrines and the incidence of environmental-based diseases in Muara Kumpe. Methods: This study is an observational analytic study that used a cross-sectional design. Samples were 100 households in Muara Kumpe, simple random sampling. Data were collected by direct observation with a checklist and questionnaire. Diseases observed within the last 6 months: Dengue Fever/DHF, Diarrhea, Malaria, TBC, Acute respiratory infection, typhoid, itchy complaint. Results: A total of 69% of households had an environmental-based disease in the last 6 months, households that meet all the criteria for healthy latrines are 14%, households with healthy domestic sewerage (HDS) are 42%, households that meet all the criteria for a good waste disposal facility are 21%. Households that meet all the criteria for clean water are 76%. There is a significant effect of healthy domestic sewerage and clean water to environmental disease. Conclusion: Improving on-site latrine quality can deliver health benefits when latrine use practices are in place Keywords: Latrine, environment, disease